Exploring the Ultrafast Charge Carrier Dynamics in Two Dimensional Heterosystems using Transient Absorption Spectroscopy for Solar Energy Applications - Himanshu Bhatt (My University, 2025)
The rapid industrialization and population growth worldwide has accelerated the depletion of fossil fuels, leading to an alarming rise in greenhouse gas emissions and global climate change. Addressing these challenges demands the exploration of renewable energy sources, particularly solar energy, which is abundant and sustainable. Among various nanomaterials, two dimensional (2D) materials have garnered considerable attention for solar energy conversion due to their unique optoelectronic and structural properties. These materials, when combined with similar and other dimensional materials (0D, 1D, and 3D), form heterostructures that enhance their applications and performance in energy harvesting technologies. This thesis investigates the interfacial photophysical phenomena occurring in various 2D heterostructures, with a focus on improving their efficiency in solar energy applications. The photophysical processes are tracked using transient absorption (TA) spectroscopy, a technique capable of probing ultrafast events on femtosecond to nanosecond timescales. The studies presented aim to establish a clear understanding of the correlation between charge carrier dynamics and the enhanced performance of these heterosystems in photocatalysis and optoelectronic applications. In the first study, a 2D/2D g-C3N4 (CN)/ZnIn2S4 (ZIS) heterostructure is synthesized, and a direct relationship between the excited-state charge carrier dynamics and enhanced photocatalytic hydrogen evolution is demonstrated. TA spectroscopy reveals that hot electron transfer from CN to ZIS dominates over band-edge electron transfer, with the rapid hot electron transfer (~0.5 ps) contributing to improved photocatalytic performance. The second study examines a 1D/2D heterojunction composed of CdS nanorods (CdS NRs) and g-C3N4 nanosheets (CN NSs). TA investigations confirm the transfer of hot electrons from CN to CdS, which improves the electron population on the CdS side in the heterojunction. This enhancement leads to an enhanced hydrogen evolution rate in the CdS/CN composite system. In the third study, band engineering is explored in a CsPbI3 (CPI) nanocrystals-WS2 heterosystem, where Ni doping is used to modulate the band alignment. Ultrafast TA measurements show that the introduction of Ni results in a type II band alignment between CPI and WS2, significantly improving charge separation and yielding higher photocurrent in the doped heterosystem. The fourth study develops an S-scheme heterostructure between ZIS and MoS2 nanosheets. The formation of a directional electric field and efficient interfacial charge transfer under solar irradiation enhances photocatalytic hydrogen production, with a 2.8-fold increase compared to pristine ZIS. TA spectroscopy reveals faster charge carrier decay kinetics, confirming improved charge separation within the heterostructure. In the final study, a metal semiconductor heterojunction (HJ) consisting of a gold nanofilm (Au NF) and a WS2 monolayer is synthesized. TA spectroscopy and optical-pump terahertz-probe (OPTP) spectroscopy reveal that hot plasmonic electron injection from Au into WS2 enhances the electron population and slows trion formation. This leads to a significant improvement in transient photoconductivity and charge carrier mobility, making the Au-WS2 HJ a promising candidate for next-generation optoelectronic devices. Overall, this thesis elucidates the fundamental mechanisms driving charge carrier dynamics in 2D heterostructures, offering insights into their optimization for energy conversion technologies.
Keywords: Heterosystems